Peran Audit Berbasis Teknologi Informasi dalam Deteksi Fraud: Penguatan Proses Audit Internal dan Kompetensi Auditor di Era Transformasi Digital - Jawziyah Khaerullah; Peri Peri; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
The rapid acceleration of digital transformation has shifted the paradigm of internal auditing from conventional manual procedures toward technology-driven approaches that enable stronger fraud detection capabilities. This study examines the strategic role of information technology based auditing in enhancing fraud detection, reinforcing internal audit processes, and strengthening auditor competencies within increasingly complex organizational environments. The integration of digital audit tools, data analytics, and automated testing mechanisms provides auditors with broader insight into transactional patterns, real-time monitoring, and improved accuracy in identifying financial irregularities. Furthermore, the development of auditor skills through digital training programs significantly supports the reliability of audit outcomes and ensures that professionals are equipped to evaluate emerging risks. Empirical evidence and literature trends indicate that organizations adopting digital audit practices experience higher efficiency, reduced procedural errors, and strengthened internal control structures. Overall, this study highlights the importance of combining advanced technological systems with competent human resources to ensure a more responsive, preventive, and value-added auditing framework in the digital era.